2022
DOI: 10.1186/s12931-022-02052-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IgG subclass deficiency on the risk of mortality in hospitalized patients with COPD

Abstract: Background Immunoglobulin G (IgG) deficiency increases the risk of acute exacerbations and mortality in chronic obstructive pulmonary disease (COPD). However, the impact of IgG subclass deficiency on mortality in COPD is unknown. Here, we determined which IgG subclass, if any, is associated with increased risk of mortality in COPD. Methods We measured serum IgG subclass concentrations of 489 hospitalized patients with COPD who were enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A study on 59 adult patients with asthma and stable COPD in Korea found that IgG subclass deficiency was the most common phenotype (67%), followed by total IgG deficiency (20%), in which IgG3 and IgG4 were the most affected subclasses [ 15 ]. Low serum IgG levels were associated with an increased risk for recurrent acute exacerbations, lower respiratory infections, a decline in lung function, and hospitalization [ 25 , 32 ]. However, the IgG3 levels at time T1 were significantly higher than those at time T2.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 59 adult patients with asthma and stable COPD in Korea found that IgG subclass deficiency was the most common phenotype (67%), followed by total IgG deficiency (20%), in which IgG3 and IgG4 were the most affected subclasses [ 15 ]. Low serum IgG levels were associated with an increased risk for recurrent acute exacerbations, lower respiratory infections, a decline in lung function, and hospitalization [ 25 , 32 ]. However, the IgG3 levels at time T1 were significantly higher than those at time T2.…”
Section: Discussionmentioning
confidence: 99%
“…IgG1 and IgG3 were initially associated with severe disease in older adults with COVID-19 (n = 123) disease and accompanying irregularities in neutralizing antibodies (nAbs), chemokines, and T cell responses, which is an anomaly as IgG3 was previously thought to provide enhanced pathogen response [ 91 , 119 , 120 ]. However, IgG deficiency has been observed to be associated with increased mortality risk in Chronic Obstructive Pulmonary Disease (COPD) patients (n = 489) in these ratios: 56% IgG1: 27%: IgG2: 24% IgG3: 31% IgG4 [ 120 ].…”
Section: Innate Immune Systems and Sars-cov-2 Researchmentioning
confidence: 99%
“…IgG1 and IgG3 were initially associated with severe disease in older adults with COVID-19 (n = 123) disease and accompanying irregularities in neutralizing antibodies (nAbs), chemokines, and T cell responses, which is an anomaly as IgG3 was previously thought to provide enhanced pathogen response [ 91 , 119 , 120 ]. However, IgG deficiency has been observed to be associated with increased mortality risk in Chronic Obstructive Pulmonary Disease (COPD) patients (n = 489) in these ratios: 56% IgG1: 27%: IgG2: 24% IgG3: 31% IgG4 [ 120 ]. A previous study (n = 105) comparing serology of hCoV-229E, hCoV-OC43, hCoV-NL63, and hCoV-HKU1 elucidated that participants show in other hCoV antibody responses with regard to IgG that were 99%:100%:98%:91%, with IgA in nasal wash samples, detected in between 8% and 31% of participants [ 121 ].…”
Section: Innate Immune Systems and Sars-cov-2 Researchmentioning
confidence: 99%
“…Responses in SARS-CoV2 Infection IgG1 and IgG3 were initially associated with severe disease (n=123) in COVID-19 disease in older age groups with accompanying irregularities in neutralizing antibodies, chemokines and T cell responses which is an anomaly, as IgG3 was previously thought to provide enhanced pathogen responses [122,123]. However, IgG deficiency has been observed to be associated with increased mortality risk in Chronic Obstructive Pulmonary Disease (COPD) patients (n=489) in these ratios 56% IgG1: 27%: IgG2: 24% IgG3: 31% IgG4 [124]. A previous study (n=105) comparing serology of hCoV-229E, hCoV-OC43, hCoV-NL63 and hCoV-HKU1 elucidated that participants show an antibody response with respective IgG responses as 99%:100%:98%: 91% with IgA in nasal wash samples detected between 8% to 31% of participants [125].…”
Section: Isotypementioning
confidence: 99%